Stereotype reduction through humor and accommodation during imagined communication with older adults. Issue 1 (2nd January 2017) - Chen, Chien-Yu; Joyce, Nick; Harwood, Jake; Xiang, Jun
ABSTRACT: Ageism can generate conflict and harm well-being. Our paper integrates the Aging Stereotypes in Interaction model with intergroup contact theory to predict how communicative elements mediate the effect of intergenerational contact on warmth and competence stereotypes of older adults as a group. Students ( N = 288) were randomly assigned to imagine having a conversation with an older adult in one of six experimentally manipulated contact conditions: a competent/incompetent older woman, a sociable/unsociable older woman, or a moral/immoral older woman. Participants' stereotypes of older adults were affected by the characteristics of their communication partner, and this effect was mediated by specific communication behaviors imagined by the participant for two of the three trait dimensions. For perceptions of competence, overaccommodation was the key mediator. For perceptions of sociability, the key mediator was humorous communication. These mediators represent an expansion in how we understand not just the outcomes of intergroup contact, but also the communicative mechanisms through which it occurs.